Pengaruh Kualitas Produk Dan Persepsi Harga Dalam Pengambilan Keputusan Pembelian Produk Mie Sedaap - Miftahul Nur Latifa; Siti Huzaimah; Rayhan Gunaningrat (Jurnal Publikasi Ilmu Manajemen, 2024)
This research was conducted with the aim of evaluating how product quality and price perceptions can influence purchasing decisions. A quantitative approach was used in this research, with an analysis model using path analysis using SmartPLS 4.0. The use of primary data through questionnaires is for information needs that describe the truth according to reality, therefore, the information obtained through this research can provide a valuable contribution to the decision-making process. The number of samples involved was 100 respondents, who were selected using purposive sampling techniques. The research results show that product quality has a significant impact on purchasing decisions, while price perceptions also have an impact on purchasing decisions.